The Fishbowl Method to Improve the Students’ Speaking Skills - Dewanti Mulki Rahma (IAIN Salatiga, 2015)
This study deals with The Fishbowl Method to Improve the Students’ Speaking Skill (An Experimental Study in Ninth Grade Students of SMP N 2 Ambarawa in the Academic Year of 2014/2015). This research was done to answer the objectives of study, namely (1) to find out the difference of lecturing and Fishbowl method in Ninth Grade Students of SMP N 2 Ambarawa in the academic year of 2014/2015, (2) to find out the significant difference of lecturing and Fishbowl method in Ninth Grade Students of SMP N 2 Ambarawa in the academic year of 2014/2015. This research applied descriptive quantitative method. The objects were Ninth Grade Students of SMP N 2 Ambarawa in the academic year of 2014/2015, and the analyzing data were students’ speaking skill that was taught by Fishbowl Method. The sample of this research was taken 28% from population. The numbers of sample were 50 students that were divided into 2 groups. The first group was experimental group and the second group was control group. The data tested using t-test formula by comparing the mean score of pre-test and post-test from both classes. The level of significance was set equal or less than 5%. The result of this study showed that t-value 8, 511 was higher than t-table 2, 064 with the degree of freedom (df) of 24. Therefore, it could be concluded that there was significant difference of T-test between students taught by lecturing and students taught by Fishbowl method. Since t-value was higher than t-table, it meant that null hypothesis was rejected and alternative hypothesis was accepted. Thus, it could be said that Fishbowl method improved students’ speaking skill in Ninth Grade Students of SMP N 2 Ambarawa in the academic year of 2014/2015